Do differences between the training load perceived by elite beach volleyball players and that planned by coaches affect neuromuscular function? (¿Las diferencias entre la carga de entrenamiento percibida por los jugadores de voleibol de playa de élite y - Ana Denise Andrade; Mário Simim; Witalo Kassiano; José Manuel Palao; Karla de Jesus; Nycaelle Maia; Cláudio Assumpção; Alexandre Igor Araripe Medeiros (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Summary. This study aimed to verify the differences between the training load planned by coaches and that perceived by Beach Volleyball (BV) players and observe the effects on athletes’ neuromuscular function. Three female BV players and well-known coaches participated in the research and were accompanied for three training weeks in the preseason phase. Rating of perceived exertion (RPE) was collected through the 0-10 scale during a previous training session. Strength, physical fitness and tactical-technical training have been assessed with coaches and athletes’ responses 30 minutes after the end of the session. RPE Session was calculated by the product between the training duration in minutes and RPE, to estimate Internal Training Load (ITL). Neuromuscular function was assessed through Countermovement Jump (CMJ). To verify differences between coaches and athletes’ responses and vertical jump performance were used either the magnitude of differences and clinical inference. Athletes experienced lower RPE and ITL as planned by coaches in the first week of training. CMJ increased substantially from the first to the third week (with likely differences (93/03/04), standardized difference = 1.60 and 90% confidence intervals = 0.00; 3.21). We suggest that training load planned by coaches similar to that perceived by athletes have a concomitant improvement with neuromuscular performance.